2018
DOI: 10.1111/febs.14650
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for the pathogenesis of Campylobacter jejuni Hcp1, a structural and effector protein of the Type VI Secretion System

Abstract: The Type VI Secretion System (T6SS) provides enhanced virulence to Campylobacter jejuni and has been associated with a high incidence of bloody diarrhea. The hemolysin-coregulated protein (Hcp)-the hallmark of the T6SS-can act as a structural and effector protein. Unlike other T6SS-harboring bacteria, which possess multiple Hcp proteins each performing different functions, C. jejuni possesses only one Hcp protein, and its structural and functional role has not been elucidated previously. Here, we report the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…In C. jejuni, the T6SS biological functions have been associated with host colonisation, cell adhesion and invasion, survival in bile salts, contact-dependent lysis of erythrocytes, and contributing to oxidative stress (Lertpiriyapong et al, 2012;Bleumink-Pluym et al, 2013;Liaw et al, 2019). So far, Hcp has been suggested as a T6SS effector contributing to C. jejuni host cell adhesion and invasion (Lertpiriyapong et al, 2012;Bleumink-Pluym et al, 2013;Noreen et al, 2018); however, no evidence currently supports the direct contribution to these phenotypes by Hcp in isolation. Whilst few studies have indicated the prevalence of T6SS in C. jejuni (Harrison et al, 2014;Corcionivoschi et al, 2015;Ugarte-Ruiz et al, 2015), a larger comprehensive bioinformatic analysis of T6SS within C. jejuni and the identification of associated effectors are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…In C. jejuni, the T6SS biological functions have been associated with host colonisation, cell adhesion and invasion, survival in bile salts, contact-dependent lysis of erythrocytes, and contributing to oxidative stress (Lertpiriyapong et al, 2012;Bleumink-Pluym et al, 2013;Liaw et al, 2019). So far, Hcp has been suggested as a T6SS effector contributing to C. jejuni host cell adhesion and invasion (Lertpiriyapong et al, 2012;Bleumink-Pluym et al, 2013;Noreen et al, 2018); however, no evidence currently supports the direct contribution to these phenotypes by Hcp in isolation. Whilst few studies have indicated the prevalence of T6SS in C. jejuni (Harrison et al, 2014;Corcionivoschi et al, 2015;Ugarte-Ruiz et al, 2015), a larger comprehensive bioinformatic analysis of T6SS within C. jejuni and the identification of associated effectors are still needed.…”
Section: Introductionmentioning
confidence: 99%
“…Hcp is a structural protein of the T6SS and is also secreted by the T6SS. Secreted Hcp has been used as a hallmark to indicate functional T6SS [55][56][57][58]. Campylobacter jejuni also has a functional T6SS without ClpV, suggesting that it may be common for Campylobacter species to use alternative ATPase instead of ClpV in performing T6SS function [55].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated the C. jejuni T6SS may be important in host cell adherence and invasion, colonization, survival in bile salts and contact-dependent cytotoxicity toward red blood cells (Lertpiriyapong et al, 2012;Bleumink-Pluym et al, 2013). A recent study examined the structure of the TssD effector in C. jejuni and found that TssD is cytotoxic toward HepG2 human liver carcinoma cells (Noreen et al, 2018). However, whether the T6SS plays a role in the survival and infection of C. jejuni in poultry, a primary reservoir in humans is still unknown.…”
Section: Introductionmentioning
confidence: 99%